Antitumor effect of a pyrazolone-based-complex [Cu(PMPP-SAL)(EtOH)] against murine melanoma B16 cell in vitro and in vivo - Abula Ayipairi; Zhao Jing; Xu Guancheng; Li Yijie; Sun Surong (Acta Pharmaceutica)
Pyrazolone-based derivative metal complexes were reported to have cytotoxicity in some tumor cells. In this study, the antitumor effect of [Cu(PMPP-SAL)(EtOH)] (PMPP-SAL = N-(1-phenyl-3-methyl-4-propenylidene-5-pyrazolone)- salicylidene hydrazide anion) in murine melanoma B16 cells in vitro and in vivo was investigated. The results showed that [Cu(PMPP-SAL)(EtOH)] inhibited the survival of B16 cells in vitro, and the IC50 value was superior to cisplatin (DDP) (p < 0.001). B16 cell apoptosis was significantly higher in comparison to the control group (DMSO) (p < 0.01), and cell cycle arrest occurred at the G0/G1 phase. When challenged C57 BL/6J mice were treated with [Cu(PMPPSAL)(EtOH)], a smaller volume of B16 solid tumors were reported than the control group (p < 0.01), with lower positive expression indices of CD 34, vascular endothelial growth factor (VEGF) and basic fibroblast growth factor (bFGF) (p < 0.01). Moreover, the tumor growth was suppressed in mice due to the induction of apoptosis, as detected by the TUNEL assay (p < 0.001). In summary, [Cu(PMPP-SAL)(EtOH)] effectively inhibited the growth of B16 cells in vitro and in vivo due to the induction of apoptosis and the inhibition of intra-tumoral angiogenesis, demonstrating its therapeutic potential in melanoma treatment.